PERAN CONVIVIALITY DALAM MENDUKUNG TRANSFORMASI DIGITAL (STUDI PADA KOMUNITAS RITEL TRADISIONAL DI BARLINGMASCAKEB) - Fitra, Joko; Wardoyo, Eko; Reni Suci Wahyuni (Bisma: Jurnal Bisnis dan Manajemen, 2025)
Traditional retail in the Barlingmascakeb region of Central Java faces significant challenges in adopting digital technology, primarily due to limited understanding, skills, and infrastructure. This study aims to explore the role of conviviality in traditional retail communities in the Barlingmascakeb region to strengthen social interaction and collaboration among community members to accelerate digital transformation. The study uses a qualitative approach with purposive sampling, with informants consisting of active community members, community mentors, community promoters, and community retail consumers. Data were collected through participatory observation, semi-structured interviews, and documentation, and analysed using Miles and Huberman's interactive model. The results of the study show that the digital transformation process involves five stages: initiation, adoption, adaptation, integration, and transformation. Community support is crucial, including building strong interpersonal relationships, holding digitalisation business training sessions, and sharing resources. Conviviality is demonstrated through close relationships between members, active participation, openness to sharing ideas, taking the initiative to organise activities, forming social networks, and flexible norms to encourage creativity. Ultimately, conviviality plays a role in the success of traditional retail communities in the Barlingmascakeb region of Central Java.